Evaluation of acute cardiovascular effects of immediate-release methylphenidate in children and adolescents with attention-deficit hyperactivity disorder - Lamberti M (Dove Medical Press, 2015)
Marco Lamberti,1,2 Domenico Italiano,2 Laura Guerriero,1 Gessica D’Amico,3 Rosamaria Siracusano,1,4 Massimo Ingrassia,5 Eva Germanò,1 Maria Pia Calabrò,3 Edoardo Spina,2 Antonella Gagliano1 1Division of Child Neurology and Psychiatry, Department of Pediatrics, 2Department of Clinical and Experimental Medicine, 3Division of Pediatric Cardiology, Department of Pediatrics, University of Messina, Messina, Italy; 4Institution of Clinical Physiology, CNR, Pisa, 5Division of Psychology, Department of Humanities and Social Sciences, University of Messina, Messina, Italy Abstract: Attention-deficit hyperactivity disorder is a frequent condition in children and often extends into adulthood. Use of immediate-release methylphenidate (MPH) has raised concerns about potential cardiovascular adverse effects within a few hours after administration. This study was carried out to investigate acute effects of MPH on electrocardiogram (ECG) in a pediatric population. A total of 54 consecutive patients with attention-deficit hyperactivity disorder (51 males and 3 females; mean age =12.14±2.6 years, range 6–19 years), receiving a new prescription of MPH, underwent a standard ECG 2 hours before and after the administration of MPH 10 mg per os. Basal and posttreatment ECG parameters, including mean QT (QT interval when corrected for heart rate [QTc]), QTc dispersion (QTd) interval duration, T-peak to T-end (TpTe) intervals, and TpTe/QT ratio were compared. Significant modifications of both QTc and QTd values were not found after drug administration. QTd fluctuated slightly from 25.7±9.3 milliseconds to 25.1±8.4 milliseconds; QTc varied from 407.6±12.4 milliseconds to 409.8±12.7 milliseconds. A significant variation in blood pressure (systolic blood pressure 105.4±10.3 vs 109.6±11.5; P<0.05; diastolic blood pressure 59.2±7.1 vs 63.1±7.9; P<0.05) was observed, but all the data were within normal range. Heart rate moved from 80.5±15.5 bpm to 87.7±18.8 bpm. No change in TpTe values was found, but a statistically significant increase in TpTe/QTc intervals was found with respect to basal values (0.207±0.02 milliseconds vs 0.214±0.02 milliseconds; P<0.01). The findings of this study show no significant changes in ECG parameters. TpTe values can be an additional parameter to evaluate borderline cases. Keywords: ADHD, methylphenidate, cardiovascular effects, children, adolescents